Orientation-dependent optical characterization of atomically thin transition metal ditellurides. Issue 46 (19th November 2018) - Hoang, Anh Tuan; Shinde, Sachin M.; Katiyar, Ajit K.; Dhakal, Krishna P.; Chen, Xiang; Kim, Hyunmin; Lee, Suk Woo; Lee, Zonghoon; Ahn, Jong-Hyun
Abstract : Molybdenum ditellurides (MoTe2 ) have recently attracted attention owing to their excellent structurally tunable nature between 1T′(metallic)- and 2H(semiconducting)-phases; thus, the controllable fabrication and critical identification of MoTe2 are highly desired. Abstract : Molybdenum ditellurides (MoTe2 ) have recently attracted attention owing to their excellent structurally tunable nature between 1T′(metallic)- and 2H(semiconducting)-phases; thus, the controllable fabrication and critical identification of MoTe2 are highly desired. Here, we semi-controllably synthesized 1T′- and 2H-MoTe2 crystals using the atmospheric pressure chemical vapor deposition (APCVD) technique and studied their grain-orientation dependency using polarization-sensitive optical microscopy, Raman scattering, and second-harmonic generation (SHG) microspectroscopy. The polycrystalline 1T′-MoTe2 phase with quasi-1D "Mo–Mo" zigzag chains showed anisotropic optical absorption, leading to a clear visualization of the lattice domains. On the other hand, 2H-MoTe2 lattice grains did not exhibit any discernible difference under polarized light illumination. The combined aforementioned microscopy techniques could be used as an easy-to-access and non-destructive tool for a quick and solid identification of intended lattice orientation development in industry-scale MoTe2 crystal manufacturing.